Reply to Editorial on "What is a potentially damaging vaccination delay in children younger than 2 years?". Issue 8 (2nd August 2016) - Dubos, François; Gras, Pauline; Martinot, Alain
ABSTRACT: Vaccine guidelines should be followed at the best to avoid vaccine preventable diseases in children and particularly in at-risk children. The authors of the editorial rightly emphasize the risk of hepatitis B in unimmunized children. Vaccine delays are frequent and indicators of vaccine delays are needed. Thresholds that identify an important increase in relative risks are the most relevant, for hepatitis B as well.